x + 2(xp − y) + p^2 = 0
Solution;
"x+2(xp-y)+p^2=0"
"x+2xp-2y+p^2=0"
"2y=x+2xp+p^2" .....(1)
"2y=x(1+2p)+p^2" ....(1a)
Differentiate (1) with respect forms;
"2\\frac{dy}{dx}=2p=1+2p+2x\\frac{dp}{dx}+2p\\frac{dp}{dx}"
Resolve as;
"0=1+2\\frac{dp}{dx}(x+p)"
"\\frac{dp}{dx}=\\frac{-1}{2(x+p)}"
"\\frac{dx}{dp}=-2(x+p)"
"\\frac{dx}{dp}+2x=-2p"
The I.F;
"I.F=e^{\\int{2}dp}=e^{2p}"
Hence;
"x\u00d7I.F=\\int-2pe^{2p}"
"xe^{2p}=\\frac{-(2p-1)e^{2p}}{2}+c"
Therefore;
"x=\\frac{1-2p}{2}+\\frac{c}{e^{2p}}" ....(3)
Substitute (2) into (1a);
"2y=[\\frac{1-2p}{2}+\\frac{c}{e^{2p}}](1+2p)+p^2"
"y=[\\frac{1-2p}{2}+\\frac{c}{e^{2p}}]\\frac{(1+2p)}{2}+\\frac{p^2}{2}"
Comments
Leave a comment